Tunable Reflectarray Cell for Wide Angle Beam-Steering Radar Applications. (24th July 2013) - Venneri, F.; Costanzo, S.; Di Massa, G.
Abstract : An electronically tunable reflectarray element is proposed in this work to design beam-steering antennas useful for radar applications. A reduced size reflectarray unit cell is properly synthesized in order to extend the antenna beam scanning capabilities within a wider angular region. The radiating structure is accurately optimized to provide a full phase tuning range by adopting a single varactor load as phase shifter element. A 0.46 λ -reflectarray cell is designed at the frequency of 11.5 GHz, obtaining a phase agility of about 330°. The cell is successfully adopted for the design of a 21 × 21 reconfigurable reflectarray. The antenna is numerically tested for different configurations of the varactors capacitance values, and good beam-steering performances are demonstrated within a wide angular range.